2010
DOI: 10.1074/jbc.m110.150094
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrolipstatin Inhibition, Functional Analyses, and Three-dimensional Structure of a Lipase Essential for Mycobacterial Viability

Abstract: The highly complex and unique mycobacterial cell wall is critical to the survival of Mycobacteria in host cells. However, the biosynthetic pathways responsible for its synthesis are, in general, incompletely characterized. Rv3802c from Mycobacterium tuberculosis is a partially characterized phospholipase/thioesterase encoded within a genetic cluster dedicated to the synthesis of core structures of the mycobacterial cell wall, including mycolic acids and arabinogalactan. Enzymatic assays performed with purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…Sequence analysis M. tuberculosis Rv3802c comprises of 336 amino acids with a molecular mass of 35,448 Da, a lipase with significant phospholipase A and thioesterase activity [19]. Based on the experimental studies on Rv3802c essentiality and its role in the organism's cellular integrity from M. smegmatis, Rv3802c is considered to be good drug target for treating tuberculosis [28,29]. Sequence analysis reveals that Rv3802c is conserved within most of the mycobacterial species including M. leprae and no sequence homolog was found in human (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence analysis M. tuberculosis Rv3802c comprises of 336 amino acids with a molecular mass of 35,448 Da, a lipase with significant phospholipase A and thioesterase activity [19]. Based on the experimental studies on Rv3802c essentiality and its role in the organism's cellular integrity from M. smegmatis, Rv3802c is considered to be good drug target for treating tuberculosis [28,29]. Sequence analysis reveals that Rv3802c is conserved within most of the mycobacterial species including M. leprae and no sequence homolog was found in human (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…All these evidences point to the essentiality of Rv3802c. The human lipase inhibitor, tetrahydrolipstatin (http://www.drugbank.ca/drugs/DB01083), inhibits both MSMEG 6394 and Rv3802c with varied degree of inhibition drives us to search for potential inhibitors effective towards mycobacterial proteins [19,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Cut4 homologue from Mycobacterium smegmatis is also active against SM (109). M. tuberculosis Cut6, which is cell wall associated (110), also has thioesterase activity and plays a critical role in mycolic acid synthesis, which likely explains why Cut6 is conserved among mycobacteria (113,114). Interestingly, Cut6 induces an immune response in mice which protects them from aerosol challenge with a virulent M. tuberculosis strain (115).…”
Section: Acyl Hydrolases: Phospholipases a And Bmentioning
confidence: 99%
“…Conditional disruptions of MSMEG_6394, functional homolog of Rv3802c in M. smegmatis lead to loss of cell wall integrity and internal structure of cell. Recent research effort revealed that tetrahydrolipstatin, a human lipase inhibitor binds irreversibly to both MSMEG_6394 and Rv3802c and exhibting antitubercular activity [10,11]. All these evidences point to the suitability of Rv3802c as promising drug target.…”
mentioning
confidence: 99%